Landscapes of power : fron Detroit to Disney World - Zukin, Sharon (University of California, 1992)
Great social transformations mark both an end and a beginning . In the structural changes of the past twenty-years, Americans have struggled to defined which elements of their lives have been destroyed forever and which are in the process of being created. Swiftly fading from mind are the industrial prosperity that was guaranteed by U.S. dominance in the world economy and a shared middle-class way of life that was accessible by work and skill.